Y+e=93

Simple and best practice solution for Y+e=93 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y+e=93 equation:


Simplifying
Y + e = 93

Solving
Y + e = 93

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '-1e' to each side of the equation.
Y + e + -1e = 93 + -1e

Combine like terms: e + -1e = 0
Y + 0 = 93 + -1e
Y = 93 + -1e

Simplifying
Y = 93 + -1e

See similar equations:

| e(x)-4e(-x)=-3 | | 15+9x=-3+x | | 180-4x-y+10=3x | | 9x+8=15+2 | | 35+3x-11=24 | | 7x-14+4x+29=180 | | 5a+1=6a | | 3(5+3x)=x-3 | | 4y-x+10=3y | | 7x+3y-4x-8y= | | 9x-11=5x+3+18 | | 4x-y+10=3x | | 1+kx=3x^2+5x+13 | | 5x^2+53x+30=30 | | x(5-k)=12 | | 5x+89=11x-13 | | 3x+4+11x-6=180 | | 3x^2-16x+15=0 | | f(x)=4x^2-5 | | -120/(-10)= | | 12x-20=6x+29+35 | | 6x+93=12x-9 | | 12x-9=9x+9 | | 2x^7= | | 2m+7=5m-5 | | 5(6x+1)=305 | | 109-5x=22x+22 | | 13x+24=9x+56 | | 4ab(2a+b-c)= | | =(8m+7)((64(m*m))-56m+49) | | 9x+6=12x-15 | | 11x+11=4x+4+77 |

Equations solver categories